2020
DOI: 10.1055/a-1069-6795
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-responsive meningitis-arteritis in dogs in Germany: Are there epidemiological or clinical factors influencing recurrence rate?

Abstract: Objective Steroid-responsive meningitis arteritis (SRMA) is one of the most common inflammatory diseases of the central nervous system in dogs. The present study examined breed and sex predisposition factors based on the population of dogs in Germany as well as epidemiological and clinical factors regarding the relapse rate of SRMA. Material and methods Data of 153 dogs with SRMA (SRMA) were analysed retrospectively in this multicentre study. It was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
10
2
Order By: Relevance
“…Generating histological samples in the future will be very unlikely because clinical diagnosis, treatment management, and awareness of this disease reduced the mortality of SRMA in the last decades ( 44 , 46 , 88 ). Therefore, prospective clinical studies could confirm antemortem evidence of ETs in dogs measuring ET markers and correlating ET inducers in clinical accessible samples of serum and CSF such as H3Cit and cell-free DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generating histological samples in the future will be very unlikely because clinical diagnosis, treatment management, and awareness of this disease reduced the mortality of SRMA in the last decades ( 44 , 46 , 88 ). Therefore, prospective clinical studies could confirm antemortem evidence of ETs in dogs measuring ET markers and correlating ET inducers in clinical accessible samples of serum and CSF such as H3Cit and cell-free DNA.…”
Section: Discussionmentioning
confidence: 99%
“…SRMA can occur in any dog breed, but is overrepresented in Bernese mountain dogs, Boxers, Beagles ( 43 , 44 ), Nova Scotia Duck Tolling Retrievers, Weimaraners, and Petit Basset Griffon Vendéens ( 45 ). A German study showed a sex predisposition for male individuals ( 46 ), but other studies do not show significant difference in sex distribution of this disease ( 47 , 48 ). The assembly of signalment, clinical signs, and laboratory findings of CSF and blood analysis associated with a quick clinical improvement after application of immunosuppressive therapy with glucocorticosteroids and an exclusion of an infectious etiology lead to the antemortem diagnosis of SRMA ( 40 , 48 50 ).…”
Section: Introductionmentioning
confidence: 88%
“…It is suggested, in 2 retrospective studies, that their low relapse rates could be associated with combination protocols for treating SRMA, but this is controversial. 3,10,15,16 It could be T A B L E 3 Incidence rate of relapse for both treatment protocols. Incidence rate of relapse events 40 (events/100 dog-years) 58 (events/100 dog-years) 50 (events/100 dog-years)…”
Section: Discussionmentioning
confidence: 99%
“…In two studies of the clinical course of SRMA, all dogs had cervical pain on presentation, with thoracolumbar being a concurrent clinical sign in 15 and 34% of dogs; isolated lumbar pain in the absence of cervical pain was not reported in these two populations [32,33]. Description of clinical signs associated with relapses commonly report "recurrence of previous signs," cervical pain, lethargy, neurological deficits (paresis, ataxia), and fever [11,[33][34][35]. Though first relapses have been reported up to 2176 days, most occur earlier [11,32].…”
Section: Discussionmentioning
confidence: 99%